H-shaped terahertz patch antenna with metamaterials for biomedical applications - Saidi Alaoui, Kaoutar; Younes, Siraj; Jaouad, Foshi (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This paper presents the design and simulation of an H-shaped terahertz microstrip patch antenna integrated with a metamaterial (MTM) layer to enhance performance for biomedical sensing applications. The antenna modeled using high frequency structure simulator (HFSS), is optimized for 4.37 THz operation. While FR4 is used in simulations for baseline analysis, alternative low-loss substrates such as polyimide or quartz are recommended for practical THz applications. The antenna design uses an FR4 substrate with a dielectric constant of 4.4 and a thickness of 2 μm. Ground plane, feed line, and patch are made of copper material. The integration of the MTM enhance clearly the antenna characteristics. This integration helps to improve the antenna impedance matching; the reflection coefficients was enhanced from -25.01 to -63.10 dB. Additionally, this integration boost also the antenna radiation characteristics, increasing the gain from 2.62 to 3.86 dB and the directivity from 3.57 to 4.97 dB.